2018
DOI: 10.1016/j.coastaleng.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of rip current forecasts to errors in remotely-sensed bathymetry

Abstract: Sensitivity of rip current forecasts to errors in remotely-sensed bathymetry Radermacher, M.; de Schipper, M. A.; Reniers, A. J.H.M. A B S T R A C TOperational nearshore current forecasts based on numerical model simulations are gaining popularity as a measure to increase the safety of swimmers. Applying remotely-sensed bathymetry in these model simulations is often proposed in order to cope with rapidly changing nearshore bathymetry. Errors in the remotely-sensed bathymetry may negatively affect performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…If not corrected, significant errors are introduced when analyzing remotelysensed hydrodynamic data such as longshore currents, run-up or wave celerity. At the Sand Motor, a mega-scale beach nourishment in the Netherlands, Radermacher et al (2018) observed important errors in the remotely-sensed bathymetry depending on camera graze angles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If not corrected, significant errors are introduced when analyzing remotelysensed hydrodynamic data such as longshore currents, run-up or wave celerity. At the Sand Motor, a mega-scale beach nourishment in the Netherlands, Radermacher et al (2018) observed important errors in the remotely-sensed bathymetry depending on camera graze angles.…”
Section: Discussionmentioning
confidence: 99%
“…Such movements are likely to occur for a certain number of outdoor installations (Holman and Stanley, 2007;Pearre and Puleo, 2009;Radermacher et al, 2018;Vousdoukas et al, 2011). Thereby, each image requires a specific geometry solution (tilt, roll and azimuth value) calculated after acquisition assuming camera location and intrinsic parameters remain the same.…”
Section: Introductionmentioning
confidence: 99%
“…Wave-averaged currents are a fundamental driver of numerous nearshore processes, including rip currents that claim lives [1], alongshore currents impacting ecosystem health and pollutant transport [2], and flow gradients altering nearshore morphology [3]. Flows can be forced by breaking wave momentum [4], pressure gradients, and low-frequency motions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although present techniques can filter, average, and smooth velocities to retain realistic alongshore flows [13,17,20], the data file sizes and associated computing power necessary for processing prohibits continuous monitoring, timely assimilation to now-cast hydrodynamic models, and real-time early warning systems of persistent and transient rip currents. The objectives of this work are (1) to define an alternate approach, referred to henceforth as WAMFlow, to remotely derive flow features at spatial and temporal scales larger than turbulent structures associated with individual waves (Section 2), (2) to validate the method with drifter deployments that contextualize the spatial variability in flow (Section 3), and (3) to highlight the potential for the technique to contribute new insights to surf zone hydrodynamics (Section 4).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of drivers or boundary conditions, hydrodynamics such as wave conditions or tides are often measured frequently or can be approximated relatively accurately through wave or tidal models. Bathymetry, on the other hand, is often unknown or outdated, such that numerical models, that are all sensitive to bathymetry accuracy, will perform poorly and cannot be trusted [4,5]. This is a particular problem, as the focus shifts to coastal response of the world's coastlines to climate change [6,7].…”
Section: Introductionmentioning
confidence: 99%